Pengaruh Tekanan Refrigeran R-134a Terhadap Nilai Coefficient of Performance (COP) - Ahmad Imam Rifa’i; Novarini (Jurnal INOVATOR, 2020)
Refrigeran is a major component in an Air Conditioner (AC) system. AC is a cooling system used as a room temperature conditioning tool, so it is comfortable to use in indoor activities. The refrigeran pressure in the cooling system can reduce the air conditioner's ability to condition the room temperature. The purpose of this study was to determine the coefficient of performance (COP) value of refrigeran R-134a with variations in refrigeran pressure of 100, 125, and 150 psi. The parameters studied were the compressor's energy consumption, the cooling capacity, and the COP value. Energy consumption is calculated based on the compressor power multiplied by the length of time the compressor is operated. The results show that the COP value decreases with an increased operating time of the cooling system; this indicates that energy consumption increases with increasing refrigeran pressure.